Comparative studies on corrosion and tribological performance of multilayer hard coatings grown on WC-Co hardmetals. (November 2020) - Derakhshandeh, M.R.; Eshraghi, M.J.; Jam, A.; Rajaei, H.; Fazili, A.
Abstract: Multilayer TiN/TiC N/TiCN /TiC/TiN and TiN/TiC N/TiCN /TiC/Al2 O3 hard coatings with total thicknesses of 15.7 μm and 9.3 μm were deposited on WC-10Co substrates using a chemical vapor deposition system. Evaluation of surface, cross-section morphologies, chemical composition and phases of coatings were analyzed by field emission scanning electron microscopy (FESEM), energy dispersive spectrometry (EDS) and X-ray diffraction (XRD) analyses respectively. Corrosion properties were evaluated in 3.5 wt% NaCl medium using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). Tribological properties of fabricated multilayer hard coatings were evaluated using pin-on-disk tests. Results show that active dissolution of the WC-10Co occurred while the coated samples showed more anodic slopes as well as lower corrosion current densities. The corrosion current densities of 3.3 × 10 −7 A/cm 2 and 7.5 × 10 −8 A/cm 2 were obtained for the TiN/TiC N/TiCN /TiC/TiN and TiN/TiC N/TiCN /TiC/Al2 O3 coated specimens which are much lower than 4 × 10 −6 A/cm 2 of substrate. EIS analysis confirmed the results of potentiodynamic polarization curves. Delamination of the TiN coating and formation of titanium oxide compounds on the surface of the TiN/TiC N/TiCN /TiC/TiN coating revealed that oxidative wear mechanism is dominant for this sample, while adhesive wear mechanism was dominant for the TiN/TiC N/TiCN /TiC/Al2 O3 coated sample. Highlights: Active dissolution of the uncoated sample was observed while the coated samples showed more corrosion resistance. The TiN/TiC N/TiCN /TiC/Al2 O3 coated sample exhibited more corrosion resistance than TiN/TiC N/TiCN /TiC/TiN coated sample. The coated specimens showed lower COF than the uncoated sample. TiN top layer showed oxidative wear mechanism while adhesive wear was predominant for Al2 O3 top layer.